Bulk Assembly of Corrugated 1D Metal Halides with Broadband Yellow Emission. Issue 6 (15th January 2019) - Lin, Haoran; Zhou, Chenkun; Neu, Jennifer; Zhou, Yan; Han, Dan; Chen, Shiyou; Worku, Michael; Chaaban, Maya; Lee, Sujin; Berkwits, Ella; Siegrist, Theo; Du, Mao‐Hua; et al.
Abstract: The family of molecular level low‐dimensional organic metal halide hybrids has expanded significantly over the last few years. Here a new type of 1D metal halide structure is reported, in which metal halide octahedra form a corrugated double‐chain structure via nonplanar edge‐sharing. This material with a chemical formula of C5 H16 N2 Pb2 Br6 exhibits a broadband yellow emission under ultraviolet light excitation with a photoluminescence quantum efficiency of around 10%. The light‐yellow emission is considered to be attributed to self‐trapping excitons. Theoretical calculations show that the unique alignment of the octahedra leads to small band dispersion and large exciton binding energy. Together with previously reported 1D metal halide wires and tubes, this new bulk assembly of 1D metal halides suggests the potential to develop a library of bulk assemblies of metal halides with controlled structures and compositions. Abstract : A novel molecularly 1D metal halide C5 H16 N2 Pb2 Br6 is discovered, in which metal halide octahedra employ a double‐chain structure in the bulk crystals. C5 H16 N2 Pb2 Br6 exhibits a broadband yellow emission with a photoluminescence quantum efficiency of ≈10% due to exciton self‐trapping.